2014
DOI: 10.1007/978-3-319-09411-3_45
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective Optimization of Mechanisms with Clearances in Revolute Joints

Abstract: Despite extensive work on the evaluation of the dynamic performances of various mechanisms and multi-body mechanical systems with revolute joint clearances, limited work has been conducted in optimizing the performances of these systems. A multi-objective optimization technique is presented to examine and to quantify the effect of combined objective functions with several design variables on the response of the systems. In particular, a Kriging meta-model based on the Design-of-Experiment method is utilized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Establish optimization variables for all hinge points involved in the working device of the grader and correlate the relationships among variables [6][7] ,to ensure that there is only one optimization variable for the same parameter and make sure that the constraint pair can move with it.…”
Section: 2determination Of Design Variablesmentioning
confidence: 99%
“…Establish optimization variables for all hinge points involved in the working device of the grader and correlate the relationships among variables [6][7] ,to ensure that there is only one optimization variable for the same parameter and make sure that the constraint pair can move with it.…”
Section: 2determination Of Design Variablesmentioning
confidence: 99%
“…To reduce the effect of the clearance on the dynamic behavior of the mechanism, several authors used optimization techniques to find the best parameters of the mechanism. The authors of [19] used the clearance in the joint and the stiffness of the material as design variables to improve the dynamic response of a crank slider mechanism. The authors of [21], [22], [23], and [25] proposed modifying…”
Section: Four-bar Mechanism With a Springmentioning
confidence: 99%
“…To reduce the effect of the clearance, several authors formulated the problem as an optimization problem ( [14], [16], [19], [20], [21], [22], [23], [24], [25], [26]). Singleobjective and multi-objective optimization problems were addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that the joint clearances have considerable effects on the displacement and velocity of the moving platform, and have great influence on the acceleration and driving moments. Zhang et al [29] presented a multiobjective optimization problem in which the effect of the clearance on the slider acceleration, contact force and power consumption was investigated. For more information on the optimization of the mechanical systems with clearance, the reader is referred to [4][5][6]30].…”
Section: Introductionmentioning
confidence: 99%